2020
DOI: 10.1186/s12887-020-02045-5
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of accessing respite care for children with Autism Spectrum Disorder (ASD) at the acute and primary care interface: a systematic review

Abstract: Background: Population prevalence estimates by the World Health Organisation suggest that 1 in 160 children worldwide has an Autism Spectrum Disorder (ASD). Accessing respite care services for children with an ASD can often be a daunting and exhaustive process, with parents sometimes forced to access acute hospital services as an initial point of contact for respite care or in a crisis situation. To gain an in-depth understanding of accessing respite care for children with an ASD, from the perspectives of pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…This association needs to be assessed carefully, however, as there were only fifteen officers represented in our study population and the input from these officers may not be reflective of the military officer population as a whole. A recent systematic qualitative review of parental perceptions and individual experiences with respite services expounded upon some of the major barriers parents face in accessing available respite care resources for their child with ASD (Cooke et al, 2020 ). This review highlights the need for families with autism spectrum disorder children to receive better education and counseling on the benefits of respite care; and the need to dispel emotional barriers to seeking out help and resources.…”
Section: Discussionmentioning
confidence: 99%
“…This association needs to be assessed carefully, however, as there were only fifteen officers represented in our study population and the input from these officers may not be reflective of the military officer population as a whole. A recent systematic qualitative review of parental perceptions and individual experiences with respite services expounded upon some of the major barriers parents face in accessing available respite care resources for their child with ASD (Cooke et al, 2020 ). This review highlights the need for families with autism spectrum disorder children to receive better education and counseling on the benefits of respite care; and the need to dispel emotional barriers to seeking out help and resources.…”
Section: Discussionmentioning
confidence: 99%
“…Increased stress levels and lower levels of well-being of parents of children with ASD were confirmed by a large number of studies [29] in comparison with parents of neurotypical children or children with other forms of disability [30][31][32][33]. Furthermore, it could often lead to burnout, depression, and psychological and physical breakdown, a condition that is exacerbated by deficits in services and general childcare [26,27,34].…”
Section: Introductionmentioning
confidence: 90%
“…This causes many parents to avoid going out and adopt a different lifestyle. Studies have shown that some parents, due to the severe stress imposed by long-term, extensive care provision, completely withdraw from social life due to the child's behavioral problems and the conflicts caused when others try to deal with the autistic child (23). Research has shown that negative judgments by others increase depression, anger, and stress in parents (6).…”
Section: Discussionmentioning
confidence: 99%